PERBANDINGAN PENYELESAIAN SENGKETA PEMUTUSAN HUBUNGAN KERJA DALAM HUKUM INDONESIA DAN HUKUM SINGAPURA: Comparison Of Employment Termination Dispute Resolution In Indonesin Law And Singaporean Law - Putri Qurrota'aini; Yogo Pamungkas (Faculty of Law, Universitas Trisakti, 2025)
Disputes between employers and employees can lead to industrial relations disputes. Indonesia as a country that adheres to the Civil Law legal system, uses Law No. 2/2024 as the legal basis regarding industrial relations disputes, while Singapore adheres to the Common Law legal system, using the Singapore Employment Act 1968 (Chapter 91) as the legal basis related to employment. The difference in the scope of authority between Indonesia and Singapore in the context of the authority of arbitration institutions shows differences in approaches to resolving labor disputes in the two countries. Identification problem that arises is how the advantages and disadvantages of resolving labor termination disputes in Indonesian law and Singapore law. This research uses normative legal research with secondary data. The nature of the research is descriptive and the conclusion is drawn by deductive method. Based on the results and the conclusio of the research when viewed from the similarities and differences between the settlement of employment termination disputes in Indonesian law and Singaporean law, Indonesia has the advantage of simplicity and independence of mediation, while Singapore highlights the advantages through more sophisticated and specialized mechanisms in resolving employment termination disputes.